THE REFUGEE CRISIS, BREXIT AND THE RISE OF POPULISM: MAJOR OBSTACLES TO THE EUROPEAN INTEGRATION PROCESS - Valeri Modebadze (Journal of Liberty and International Affairs, 2019)
This article describes the main challenges that the European Union is facing over the last years. It also analyzes the European integration process and the emergence of the European Union. European integration process began after the Second World War. European politicians realized that 'the old continent', which was destroyed and razed to the ground, needed unification in order to play more important role in the bipolar international system. The European integration was a step by step process, which reached its culmination after signing the Maastricht Treaty in 1992, when the European Union was formally established. The European Union created very favorable ground for free movement of people, goods, services and capital within the internal market. Despite these positive developments, new threats emerged over the last years that can put an end to the European integration process. From these threats and challenges, particular attention is dedicated to Britain's exit from the European Union (Brexit), rise of radicalism and populist parties, migration crisis and a heightened terrorism threat.